Reclaiming Jesus as source of peace in Luke 12:49–53 through the perspective of religious pluralism in an Indonesian context - Parihala, Yohanes (HTS teologiese studies, 2020)
The reality of religious pluralism such as that possessed by the Indonesian people could be an opportunity to knit a peaceful togetherness, or it could be a threat and a trigger for conflict. One threat to the diversity of religions stems from religious teachings that tend to be exclusive in nature by emphasising the justification of one’s own religion and viewing different religions as a challenge, even as the enemy. In the teachings of every religion, there are sacred texts, which, if read literally, can be texts of terror that give rise to permissive attitudes towards various acts of violence, hatred and hostility in the name of religion. This research aims to find the theological vision of the Gospel of Luke 12:49–53 and to explain its relevance in relation to the reality of religion and peace in the context of the pluralistic society in Indonesia. This research uses qualitative research methods through a literature study approach. The data analysis uses half of the historical criticism method, which starts from the translation of the text with our criticism of the sources behind the text, and then moves to an analysis of the historical context as the background of the text. Furthermore, exegesis is done to explore the meaning of Luke 12:49–53.Contribution: This article contributes to developing the contextual hermeneutics of the text Luke 12: 49–53 and reclaiming Jesus as the source of peace which inspires the peaceful relationship between religions in the context of religious pluralism such as in an Indonesian context.